2018
DOI: 10.1155/2018/3985154
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Levels in Fibromyalgia and Their Response to 15 Weeks of Progressive Resistance Exercise or Relaxation Therapy

Abstract: The aims of this study were to compare circulating cytokines between FM and healthy controls and to investigate the effect on cytokine levels by 15 weeks of progressive resistance exercise or relaxation therapy in FM. Baseline plasma cytokine levels and clinical data were analyzed in 125 women with FM and 130 age-matched healthy women. The FM women were then randomized to progressive resistance exercise (n = 49) or relaxation (n = 43). Baseline IL-2, IL-6, TNF-α, IP-10, and eotaxin were higher in FM than in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(126 citation statements)
references
References 60 publications
(90 reference statements)
6
118
0
2
Order By: Relevance
“…inflammatory cytokines. 12,13 However, there have been inconsistencies in these findings with results from previous studies (i.e., plasma levels of various catecholamines have been increased, decreased, or unchanged). 14 Despite intensive research focusing on multiple biologically plausible markers to aid in the diagnosis and prognostication of disease activity in FM, further understanding of the biological perturbations is needed to better explain potential underlying mechanisms related to FM and to guide personalized health strategies for symptom management.…”
Section: Metabolomic Differentials In Fibromyalgiamentioning
confidence: 71%
See 1 more Smart Citation
“…inflammatory cytokines. 12,13 However, there have been inconsistencies in these findings with results from previous studies (i.e., plasma levels of various catecholamines have been increased, decreased, or unchanged). 14 Despite intensive research focusing on multiple biologically plausible markers to aid in the diagnosis and prognostication of disease activity in FM, further understanding of the biological perturbations is needed to better explain potential underlying mechanisms related to FM and to guide personalized health strategies for symptom management.…”
Section: Metabolomic Differentials In Fibromyalgiamentioning
confidence: 71%
“…A variety of physiological factors are purported to be involved in the pathophysiology of FM, including genetic vulnerability, altered levels of neurotransmitters, and immune system/inflammatory factors; however, no one etiologic target or set of targets has been determined . For example, researchers have suggested that chronic low‐grade systemic inflammation may contribute to both the initiation and maintenance of the centralized pain state, focusing their studies on peripheral blood markers in FM, including inflammatory cytokines . However, there have been inconsistencies in these findings with results from previous studies (i.e., plasma levels of various catecholamines have been increased, decreased, or unchanged) …”
mentioning
confidence: 99%
“…As described above, there were originally 260 participants in the multi-centre study: 130 women with FM and 130 HC. Plasma levels of cytokines and chemokines for the total cohort were previously analysed (28). Plasma samples from 100 participants were available for analysis of NGF and BDNF and consequently only those subjects were included in this study; 75 out of the 100 were women with FM and 25 were HC.…”
Section: Subjectsmentioning
confidence: 99%
“…Psychometric variables and PPT were registered at baseline (both FM and HC) and after the interventions (only in FM). Data have previously been presented for the total cohort (FM: n = 130 and HC: n = 125) (28,31). Details about the variables are presented in those studies (28,31).…”
Section: Variables Registeredmentioning
confidence: 99%
See 1 more Smart Citation